TRAINING ON EARLY STUNTING DETECTION USING WEB AND R-SHINY APPLICATIONS FOR COMMUNITY HEALTH WORKERS (POSYANDU) IN THE SONGGON COMMUNITY HEALTH CENTER CATCHMENT AREA, BANYUWANGI REGENCY - Nur Chamidah; Ardi Kurniawan; Toha Saifudin; Raaulia Gita Nafsi; Mia Khoirunnisa; Fa’iqotus Zuqna Dwi Syauqie; Dwika Maya Harsanti; Verina Tita Nabila; Naufal Ramadhan Al Akhwal Siregar (Jurnal Layanan Masyarakat (Journal of Public Services), 2026)
Stunting is a condition that reflects the nutritional status of toddlers and serves as a crucial indicator for monitoring their growth and development. The prevalence of stunting in East Java Province was recorded at 19.2% in 2022, indicating that the province still faces serious challenges requiring sustained intervention. However, monitoring efforts at the local level, particularly within the Songgon Public Health Center (Puskesmas) working area, still encounter technical obstacles such as inconsistent and inaccurate nutritional data recording systems, which risk compromising the validity of early detection. To address these issues, this community service activity aimed to equip Posyandu cadres with nutritional knowledge and technical skills in utilizing a Web-based and R-Shiny early detection application. The application allows users to input toddler anthropometric data (Weight-for-Age, Height-for-Age, and BMI-for-Age) and automatically generates growth charts based on reference standards. It also integrates National Identification Number (NIK) inputs to ensure data validity and prevent duplication. The activity was conducted on August 2, 2025, involving 49 cadres from the Songgon Health Center working area. Evaluation results showed a significant increase in competence, marked by a higher average post-test score (90.204) compared to the pre-test score (77.007), with a paired t-test p-value of 0.000. Participants' satisfaction levels were also categorized as excellent, with average scores exceeding 85 across all indicators. Through intensive mentoring and an accurate local data-driven approach, this program is expected to serve as an adaptive, modern community service model that can be replicated to accelerate stunting reduction.